Pengaruh Budaya Organisasi, Kepemimpinan Dan Komitmen Terhadap Produktivitas Kerja Karyawan ( Studi Pada PT Astra International Tbk Daihatsu Cabang Majapahit Semarang ) - Agustin, Novianti; Nugraha, Hari Susanta; Budiatmo, Agung (Jurnal Ilmu Administrasi Bisnis, 2015)
AbstractEmployee productivity is one measure that is often used to determine the efficiency and effectiveness of the organization. An organization or company can’t develop if the productivity of employees does not increase especially with the high level of competition that exists in the business world. Organizational culture, leadership and commitment have an influence in increasing employee productivity. Therefore, three things need to be considered in order to increase productivity of employees. PT. Astra International Tbk Daihatsu Majapahit Semarang Branch is one private enterprise which engaged in the sale and repair of Daihatsu brand car. This type of research is explanatory research. The population in this study are the employee of PT Astra International Tbk Daihatsu Majapahit Semarang Branch. Sample calculation using probability sampling technique with respondents as many as 65 people. Data collection techniques in this research using interview techniques, questionnaire and literature study. The data obtained were analyzed quantitatively by using analytical tools in the form of the cross table, validity, reliability, simple linear regression, multiple linear regression and hypothesis testing by t test and F test.            The conclusion from this study is that there are influence between organizational culture, leadership and a commitment on work productivity at PT Astra International Tbk-Dihatsu, Majapahit Semarang Branch. The organizational culture was 38%, the leadership was 44.9%, and the commitment was 30.1%. Mutual influence the organizational culture, leadership and a commitment by 47.7%, while 52.3% is influenced by other factors. Advice: the company need to increase productivity of employees through increased cultural organizations by instilling cultural values, raise the skills of employees of one of them through training, the leader must be able to motivate the group to discuss the issue before making a decision that reflects the mutual consent of all members of the group and can increase the sense of responsibility as an employee commitment to the company.